How Effective is Regional Spatial Detail Plans as Instrument of Flood Management (Case Study:Kedurus Watershed,Surabaya City) - Lukman Yusuf; Adjie Pamungkas; Eko Budi Santoso (IPTEK Journal of Proceedings Series, 2020)
Surabaya city has detailed spatial planning documents as instruments for flood reduction. The detailed spatial plan for the area regulates land use plans to prevent uncontrolled land use changes that cause flooding. The research question is "What is the efficiency of the detailed spatial plan as an instrument for flood management in the Kedurus River Basin?". The analysis tool is the spatial modeling of floods based on 2D Flow Area using HEC RAS 5 software. The first step is to build a spatial flood model using the existing condition parameters, the next step is to apply the parameters derived from the detailed spatial plan in the Kedurus River Basin on the models that have been built . The result is that the implementation of detailed regional spatial plans in the Kedurus watershed tends not to reduce the area of flood inundation even on the contrary increases the runoff coefficient. In the spatial model of flooding it is known that the condition of the return period of 20 years also shows an increase in the area of flood inundation to 0.5-1 meters from the existing condition which initially covered an area of 45.92 Ha to 72.38 Ha.